Molecular mechanisms of water table lowering and nitrogen deposition in affecting greenhouse gas emissions from a Tibetan alpine wetland - Hao Wang; Lingfei Yu; Zhenhua Zhang; Wei Liu; Litong Chen; Guangmin Cao; Haowei Yue; Jizhong Zhou; Yunfeng Yang; Yanhong Tang; Jin‐Sheng He (Global Change Biology, 2017)
Rapid climate change and intensified human activities have resulted in water table lowering ( WTL ) and enhanced nitrogen (N) deposition in Tibetan alpine wetlands. These changes may alter the magnitude and direction of greenhouse gas ( GHG ) emissions, affecting the climate impact of these fragile ecosystems. We conducted a mesocosm experiment combined with a metagenomics approach (GeoChip 5.0) to elucidate the effects of WTL (−20 cm relative to control) and N deposition (30 kg N ha −1 yr −1 ) on carbon dioxide ( CO 2 ), methane ( CH 4 ) and nitrous oxide (N 2 O) fluxes as well as the underlying mechanisms. Our results showed that WTL reduced CH 4 emissions by 57.4% averaged over three growing seasons compared with no‐ WTL plots, but had no significant effect on net CO 2 uptake or N 2 O flux. N deposition increased net CO 2 uptake by 25.2% in comparison with no‐N deposition plots and turned the mesocosms from N 2 O sinks to N 2 O sources, but had little influence on CH 4 emissions. The interactions between WTL and N deposition were not detected in all GHG emissions. As a result, WTL and N deposition both reduced the global warming potential ( GWP ) of growing season GHG budgets on a 100‐year time horizon, but via different mechanisms. WTL reduced GWP from 337.3 to −480.1 g CO 2 ‐eq m −2 mostly because of decreased CH 4 emissions, while N deposition reduced GWP from 21.0 to −163.8 g CO 2 ‐eq m −2 , mainly owing to increased net CO 2 uptake. GeoChip analysis revealed that decreased CH 4 production potential, rather than increased CH 4 oxidation potential, may lead to the reduction in net CH 4 emissions, and decreased nitrification potential and increased denitrification potential affected N 2 O fluxes under WTL conditions. Our study highlights the importance of microbial mechanisms in regulating ecosystem‐scale GHG responses to environmental changes.